2016
DOI: 10.1007/s10597-016-0029-z
|View full text |Cite
|
Sign up to set email alerts
|

Comorbid Depression and Other Predictors of PTSD Severity in Urban Public Transit Employees

Abstract: The purpose of the study was to determine whether post traumatic stress disorder (PTSD) with Major Depressive Disorder (MDD) among urban public transit employees who were exposed to a workplace traumatic event is associated with greater PTSD severity over the 6-month follow-up period compared to PTSD without MDD, and also to identify predictors of PTSD severity among these employees. Information about Axis-I diagnosis and PTSD severity were collected from the SCID-I and the Modified PTSD Symptom Scale (MPSS) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…After an industrial explosion, the risk factors of PTSD among the nearby workers included trauma, history of mental disorder or occurrence of psychiatric symptoms at the time of the event [15,16], proximity to explosion site, nonmanagerial occupation, age over 50 years in both sex, layoffs (aOR = 2.6; 1.5-4.5), and unusable workplace after the explosion (aOR = 1.8; 1.1-2.8) in men [17]. A Canadian study evaluating the health of urban public transit employees after experiencing traumatic events at the workplace indicated difference in PTSD severity according to the severity of depression, gender, ethnicity, and workplace stress [18].…”
Section: Risk Factors Of Ptsd Among Workersmentioning
confidence: 99%
“…After an industrial explosion, the risk factors of PTSD among the nearby workers included trauma, history of mental disorder or occurrence of psychiatric symptoms at the time of the event [15,16], proximity to explosion site, nonmanagerial occupation, age over 50 years in both sex, layoffs (aOR = 2.6; 1.5-4.5), and unusable workplace after the explosion (aOR = 1.8; 1.1-2.8) in men [17]. A Canadian study evaluating the health of urban public transit employees after experiencing traumatic events at the workplace indicated difference in PTSD severity according to the severity of depression, gender, ethnicity, and workplace stress [18].…”
Section: Risk Factors Of Ptsd Among Workersmentioning
confidence: 99%
“…Completion of this quality review resulted in an automatically-computed numeric score out of 10, with higher scores reflecting higher quality studies. This numeric score was converted to a categorical quality score of low (0-4), medium (5-7), or high quality (8)(9)(10) according to the categorical guidelines employed by the Health Evidence Assessment tool. 30 Additional details of the systematic review procedure are reported elsewhere in depth.…”
Section: Data Extractionmentioning
confidence: 99%
“…This variability may be attributable to any number of factors including occupation-specific variance, 2 methodological factors, 3 regional differences in prevalence, 4 or other systematically variable factors such as organizational and individualdifference factors. [5][6][7][8][9] Such heterogeneity of prevalence outcomes poses a significant obstacle to the reliability and interpretability of traditional meta-analytic approaches 10 evaluating prevalence of trauma-related mental health conditions in high-risk personnel on a global scale. To date, the potential contributing sources to variability in prevalence outcomes across the literature have been drastically under-studied.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation